Indices of 3-hour pH-metry in young overweighed patients with GERD - I. Yu. Usanova; N. M. Kozlova; G. P. Lyakh (Acta Biomedica Scientifica, 2013)
In the study there were 35 overweighed patients with GERD (study group - SG), clinical comparison group (CCG) consisted of 20 standard patients with GERD. Alkaline reflux was revealed in 22 patients (62 %) of SG and 7 patients (33 %) of CCG, while acid reflux was revealed in 13 persons (38 %) of SG and 13 persons (67 %) of CCG. The comparison of the groups showed that the alkaline reflux was more common in patients of SG, significant differences were determined between the acidity rate in an esophagus at rest and during stimulation (p < 0,05). In patients of the groups with acid reflux significant differences were determined in the esophagus at rest and during stimulation (p < 0,05), in forestomach - at rest and after stimulation (p < 0,05). In overweighed patients complaining of heartburn alkaline reflux is more common while patients with normal weight have acid reflux. In SG life activity (p < 0,05), social function (p < 0,05), mental health (p < 0,05) were statistically reduced, pain in the upper epigastric severely limits daily activity (p < 0,05) compared to the CCG. Our results demonstrate that patients need to be treated of GERD in a different way considering the body weight.